Antimicrobial Usage in Horses: The Use of Electronic Data, Data Curation, and First Results - Schnepf, Anne; Bienert-Zeit, Astrid; Ertugrul, Hatice; Wagels, Rolf; Werner, Nicole; Hartmann, Maria; Feige, Karsten; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2020)
The usage of antimicrobial drugs (AMs) leads to an increase in antimicrobial resistance. Although different antimicrobial usage (AMU) monitoring programs exist for livestock animals in Germany, there is no such system for horses. However, with the increasing usage of electronic practice management software (EPMS), it is possible to analyze electronic field data generated for routine purposes. The aim of this study was to generate AMU data for German horses with data from the Clinic for Horses (CfH), University of Veterinary Medicine Hannover, and in addition to show that different processes of data curation are necessary to provide results, especially considering quantitative indices. In this investigation, the number of antimicrobial doses used and the amount and percentage of active ingredients applied were calculated. Data contained all drugs administered between the 1st of January and the 31st of December 2017. A total of 2,168 horses were presented for veterinary care to the CfH and 34,432 drug applications were documented for 1,773 horses. Of these, 6,489 (18.85 %) AM applications were documented for 837 (47.21 %) horses. In 2017, 162.33 kg of active ingredients were documented. The most commonly used antibiotic classes were sulfonamides (84.32 kg; 51.95 %), penicillins (30.11 kg; 18.55 %) and nitroimidazoles (24.84 kg; 15.30 %). In 2017, the proportion of Critically Important Antibiotics (CIA) - Highest Priority used was 0.15 % (0.24 kg) and the proportion of CIA - High Priority used was 20.85 % (33.85 kg). Of the total 9,402 entries of antimicrobial active ingredients, the three with the largest number used were sulfonamides (n=2,798 (29.76 %)), trimethoprim (n=2,757 (29.76 %)) and aminoglycosides (n=1,381 (14.69 %)). Comparison between Administered Daily Dose (ADA) and Recommended Daily Dose of CfH (RDDCfH), showed that 3.26 % of ADA were below RDDCfH, 3.18 % exceeded RDDCfH and 93.55 % were within the range around RDDCfH. This study shows that data generated by an EPMS can be evaluated once the method is set up and validated. The method can be transferred to evaluate data from the EPMS of other clinics or animal species, but the transferability depends on the quality of AMU documentation.